Analysis of Radix Guitar Marketing Strategy on Queen Guitars Gallery, Bengkulu City - Yanuardi Yanuardi; Ahmad Soleh; Eska Prima Monique Damarsiwi (Journal of Indonesian Management, 2021)
In conducting marketing activities a company has several objectives to be achieved, both short-term goals and long-term goals. In the short term it is usually to win the hearts of consumers, especially for newly launched products. Whereas in the long term it is carried out to maintain existing products in order to exist. Likewise, the Queen Guitars Gallery of the City of Bengkulu, of course, requires the role of marketing activities and strategies. Based on this, then to find out the exact strategy used by the Queen Guitars Gallery of the City of Bengkulu, a SWOT analysis is needed. The purpose of this study was to find out the marketing strategy of the Radix guitar at the Queen Guitars Gallery in the City of Bengkulu.From the results of IFAS and EFAS research in this study, there was a strength factor possessed by the Bengkulu City Queen Guitars Gallery of 25, while the weakness was 6.69. So the internal quadrant of the factor is 25-6.69 = 18.31, while the opportunity factor that is owned is 19.125 and for the threat factor is 7,15. So the external quadrant is a factor of 19.125-7,15 = 11,975. Based on this analysis, Queen Guitars Gallery of the City of Bengkulu is in quadrant 1 in the SWOT diagram. Based on the results of research carried out at the Bengkulu City Queen Guitars Gallery, it can be concluded that the appropriate strategy is an aggressive strategy or Strength opportunity (SO) strategy, because the Bengkulu City Queen Guitars Gallery currently has great strength and opportunity, so this strategy which can be used for the progress of the Queen Guitars Galllery City of Bengkulu.